2019
DOI: 10.1177/0954406219868500
|View full text |Cite
|
Sign up to set email alerts
|

Fluid–solid coupling numerical simulation for the performance prediction and valve dynamic analysis of a rotary compressor

Abstract: To predict the performance of a rotary compressor and study the dynamic coupling characteristics of the valve, a three-dimensional dynamic model of the compressor is constructed in this paper. The model adopts the fluid–solid interaction method and the dynamic grid technique to achieve coupled reed valve motion. Meanwhile, to solve the problem of grid deformation caused by large deformation of the valve plate, a user-defined dynamic grid method is used to realize grid updating in the deformed area based on com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…In order to apply the abradable coating on rotors of the twin-screw compressor without affecting the reliable operation of the compressor, it is necessary to study the temperature distribution and pressure distribution of the rotor surface, and accurately predict the deformation of rotors under the above-mentioned multiple alternating physical effects by using the fluid-solid coupling method. 17 The temperature distribution and pressure distribution of the rotor surface are obtained by CFD simulation, and the results of deformation are shown in this section.…”
Section: Deformation Analysis Of the Rotors Based On Fluid-solid Coupling Methodsmentioning
confidence: 99%
“…In order to apply the abradable coating on rotors of the twin-screw compressor without affecting the reliable operation of the compressor, it is necessary to study the temperature distribution and pressure distribution of the rotor surface, and accurately predict the deformation of rotors under the above-mentioned multiple alternating physical effects by using the fluid-solid coupling method. 17 The temperature distribution and pressure distribution of the rotor surface are obtained by CFD simulation, and the results of deformation are shown in this section.…”
Section: Deformation Analysis Of the Rotors Based On Fluid-solid Coupling Methodsmentioning
confidence: 99%
“…Acoustical analyses were carried out and found that discharge pulsation due to its cyclic discharge nature was the main source of noise instead of mechanical vibration [127][128][129][130]. An FSI simulation of the discharge valve [131] noted that the impact of the valve against the valve stop contributed to the noise as well. Noise arising from vibration of the components can be mitigated by directly reducing vibration, such as using dampers [116] or reinforcing the compressor housing and internal mounting structure [129].…”
Section: Compressor Dynamics and Vibrationmentioning
confidence: 99%
“…Additionally, it also causes over-compression loss since more work is required to actuate the discharge valve. This was studied both analytically [132,133], experimentally [77,134], and with CFD simulations [130,131,135]. Methods to reduce loss would be to increase the number of discharge ports [136] or to implement valves that are easier to actuate, such as thinner and longer reed valves [137].…”
Section: Valve Mechanics and Port Flowmentioning
confidence: 99%
“…[1,2] Rotary compressors are widely used in household air conditioners with their compact structure and excellent performance. [3,4] In past decades, many scholars would pay more attention to different types of leakage losses in the cylinder to enhance the thermal performance and improve the efficient of rotary compressor system. Cai et al [5,6] and He et al [7] conducted a theoretical method to calculate several kinds of leakage losses in rotary compressor and proposed the experimental investigation to compare the theoretical results with experimental results, which proved the validity of theoretical method.…”
Section: Introductionmentioning
confidence: 99%